Perspectives of parents receiving normal results from genomic newborn screening: a mixed-methods evaluation from the early check program - Gwaltney, Angela Y.; Halpin, Sean N.; Scott, Samantha; Andrews, Sara M.; Okoniewski, Katherine C.; Cope, Heidi L.; Raspa, Melissa; Scharfe, Curt; Peay, Holly (Frontiers in Genetics, 2025)
As genomic technologies become increasingly practicable for public health application, research programs are exploring population-scale genomic newborn screening (gNBS). Early Check is a statewide newborn screening research program in North Carolina that offers optional whole genome sequencing-based screening to parents of newborns through an electronic education, consent, and return of results platform. Parents can elect to receive screening for over 200 monogenic conditions and risk for type 1 diabetes (T1D) using a genetic risk score (GRS). To address knowledge gaps in gNBS implementation, we conducted a concurrent mixed-methods study evaluating the feasibility, acceptability, and effectiveness of the program’s electronic education, consent, and return of results processes among participants who received normal screening results. We emailed the evaluation survey link to consenting parents of all participating newborns with screening results showing no increased risk identified (n = 3,496). Survey respondents could indicate their willingness to participate in an interview. A total of 279 surveys and 14 interviews were included for quantitative and qualitative analysis. Findings revealed high levels of satisfaction (94.8% positive attitude). Overall, levels of regret were low, with two-thirds of respondents reporting no regret and an additional quarter reporting mild regret. Nonetheless, the proportion reporting mild regret indicates that a meaningful subset experienced some degree of uncertainty or second thoughts. Additionally, there was generally moderate comprehension overall, with 60.9% of parents demonstrating adequate knowledge when assessed across key items. Parents’ frequently-endorsed motivators included learning about their baby’s future health, the study being free, and the study not requiring extra blood samples. Although most appreciated the convenience and clarity of the process, some requested more information on topics including genetic testing and T1D GRS. Parents reported limited use of the educational videos and laboratory-generated screening reports, but most viewed the lay summary of normal results. Despite this selective engagement, they described the overall experience as accessible and well-designed. Parents’ decisions to share results were primarily confined to family members, with fewer disclosures to healthcare providers. This study supports the feasibility and acceptability of large-scale electronic consent and return of results processes but highlights some challenges in comprehension and equity across diverse populations.